2018
DOI: 10.1002/nafm.10215
|View full text |Cite
|
Sign up to set email alerts
|

Air Exposure, Fight Times, and Deep‐Hooking Rates of Steelhead Caught in Idaho Fisheries

Abstract: Potential effects of air exposure and fight times on fish caught and released by anglers have been increasingly studied in recent years, yet little is known about how long anglers actually fight the fish and expose them to air before releasing them. In the present study, air exposure and fight times were measured for anglers catching and releasing fish in popular steelhead Oncorhynchus mykiss fisheries in Idaho, and other relevant factors were also recorded such as fishing gear (fly or nonfly), occurrence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Both angler‐related air exposure time and tube‐transport air exposure time observed in this study were similar to mean air exposures reported in trout and steelhead fisheries, whereas fight time was higher than those previously observed in trout fisheries but similar to those observed in other steelhead fisheries (Lamansky and Meyer ; Chiaramonte et al. ; Roth et al. ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Both angler‐related air exposure time and tube‐transport air exposure time observed in this study were similar to mean air exposures reported in trout and steelhead fisheries, whereas fight time was higher than those previously observed in trout fisheries but similar to those observed in other steelhead fisheries (Lamansky and Meyer ; Chiaramonte et al. ; Roth et al. ).…”
Section: Discussionsupporting
confidence: 90%
“…Hooking location was also not of interest in this study, but in the companion study, most fish were hooked in the mouth, and deep hooking was extremely rare (<1%; Chiaramonte et al. ). All anglers signed a volunteer form to participate, but their skill levels varied widely.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…Additional fishing regulations could be implemented in an attempt to limit catch‐and‐release mortality and generally include gear and fish handling restrictions. However, findings in the literature on the effectiveness of these regulations at meeting targets for catch‐and‐release mortality are mixed and are likely context specific (Nelson et al 2005; Chiaramonte et al 2018; Twardek et al 2018; Whitney et al 2019). Although such regulations may be effective in certain circumstances, they are likely an imprecise tool to meet management objectives compared to the other management strategies evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%